Properties of sputtered ZnS thin films for photovoltaic application - Haque F.; Rahman K.S.; Akhtaruzzaman M.; Abdullah H.; Kiong T.S.; Amin N. (Institute of Physics Publishing, 2023)
Energy gap; II-VI semiconductors; Lime; Magnetron sputtering; Optical band gaps; Optical properties; Sputtering; Substrates; Surface morphology; Surface roughness; Thin films; Topography; X ray diffraction; Zinc sulfide; Hall effect measurement; Optical and electrical properties; Photovoltaic applications; Preferential orientation; RF magnetron sputtering technique; Soda lime glass substrate; Structural determination; ZnS thin films; Optical films